2022
DOI: 10.1186/s12886-022-02580-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of lacrimal drainage pathway disease-associated keratopathy

Abstract: Purpose To report the clinical characteristics of 13 cases of noninfectious corneal ulceration related to lacrimal drainage pathway disease. Methods Medical records of 13 patients with lacrimal drainage pathway disease-associated keratopathy who were examined at Ehime University Hospital between April 2007 and December 2021 were analyzed. Results The predisposing lacrimal drainage pathway diseases for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In previous reports of six cases in which the corneal perforation site was known, perforations were observed on the nasal side. 13 , 14 , 16 However, our case series shows that corneal perforation with lacrimal canaliculitis can occur in any part of the cornea.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In previous reports of six cases in which the corneal perforation site was known, perforations were observed on the nasal side. 13 , 14 , 16 However, our case series shows that corneal perforation with lacrimal canaliculitis can occur in any part of the cornea.…”
Section: Discussionmentioning
confidence: 70%
“…In this report, all six patients with corneal perforation and lacrimal canaliculitis were female, and most of them were aged 70 years or above. Previous studies have reported two male cases and six female cases of corneal perforation associated with canalliculitis 13 , 14 , 16 , 17 It is possible that corneal perforation caused by lacrimal canaliculitis is much more common in females. A possible explanation is the preponderance of lacrimal duct diseases, including canaliculitis, in older females.…”
Section: Discussionmentioning
confidence: 98%
“…Treatment of lacrimal drainage pathway disease combined with surgical intervention or contact lens wear for corneal perforation has shown favorable outcomes in patients with corneal ulcers and perforations. [7][8][9] Patients with lacrimal drainage pathway diseases exhibit elevated levels of various in ammatory cytokines in tear uid. [16][17][18] Recanalization of the lacrimal drainage pathway may reduce the levels of interleukins and matrix metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%
“…These patients differ from patients with corneal ulcers and perforations associated with lacrimal duct obstruction, as those patients had systemic immune disorders such as rheumatoid arthritis and used topical corticosteroids. [6][7][8][9]12 The differences in patient background between corneal ulcers, perforations, and corneal epitheliopathy suggest that corneal epitheliopathy does not lead to the development of corneal ulcers or perforations, but rather each condition occurs independently in different groups of patients with tear duct disorders. In other words, corneal epitheliopathy may not be a precursor lesion to corneal ulcers or perforations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation